2001
DOI: 10.1080/019021401300317134
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intercellular Adhesion Molecule 1 in Acute Lung Injury Induced by Candidemia

Abstract: Candidemia, a complication often affecting immunocompromised patients, is a common cause of acute lung injury. Yeast-phase Candida albicans has been shown to express a protein that is antigenically and structurally related to Mac-1. C. albicans is reported to stimulate intercellular adhesion molecule 1 (ICAM-1) expression on endothelial cells. In this study, the authors examined the role of ICAM-1 in acute lung injury induced by candidemia. The authors cultured rat pulmonary artery endothelial cells (RPAEC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
2
11
0
1
Order By: Relevance
“…Although anti-ICAM-1 antibody is known to inhibit T-cell adhesion and immune function (31), it seems that the anti-ICAM-1 MAb used in this study did not modify the activation of HGECs but inhibited the direct binding of C. albicans with HGECs. Our result supported a previous report that ICAM-1 plays a role in the adherence of C. albicans to pulmonary vascular endothelial cells (34). In both studies, however, inhibition of C. albicans adhesion to host cells by anti-ICAM-1 antibody was not complete.…”
Section: Increased Induction Of Interleukin 8 (Il-supporting
confidence: 81%
“…Although anti-ICAM-1 antibody is known to inhibit T-cell adhesion and immune function (31), it seems that the anti-ICAM-1 MAb used in this study did not modify the activation of HGECs but inhibited the direct binding of C. albicans with HGECs. Our result supported a previous report that ICAM-1 plays a role in the adherence of C. albicans to pulmonary vascular endothelial cells (34). In both studies, however, inhibition of C. albicans adhesion to host cells by anti-ICAM-1 antibody was not complete.…”
Section: Increased Induction Of Interleukin 8 (Il-supporting
confidence: 81%
“…Expression of these adhesion molecules is induced by the production of pro-inflammatory cytokines such as TNF- and IL-1 (Osborn et al, 1989;Masinovsky et al, 1990), which have been reported as important inflammatory components in a variety of lung diseases including those caused by fungi (Hamacher & Schaberg, 1994;Izzo et al, 1998;Yokomura et al, 2001;Yu & Limper, 1997). In our PCM mouse model, we have observed that lungs of mice infected intranasally with P.brasiliensis conidia show a higher expression of adhesion molecules during the first 4 days post-challenge.…”
Section: Expression Of Adhesion Molecules and Extracellular Matrix Prsupporting
confidence: 53%
“…Of these molecules, only ICAM-1 and -2 are widely expressed on endothelial cells, although CD14 was recently identified on primary, but not passaged, cultures of human umbilical vein endothelial cells (49). There are no data on the role of CD14, CD102, or CD242 as a possible endothelial ligand for C. albicans adhesion, but Yokomura et al (82) have shown that anti-CD54 monoclonal antibodies can partially inhibit the adhesion of yeast forms of C. albicans to rat pulmonary artery endothelial cells in vitro and significantly prolong the survival of rats injected intravenously with C. albicans. In certain circumstances, it is also possible that ␣ M ␤ 2 ligands such as fibrinogen, heparin and iC3b could in turn bind to endothelial cells and act as an intermediary in Candida-endothelial cell adhesion.…”
Section: Candidate Candida Adhesins and Their Endothelial Ligandsmentioning
confidence: 99%